Phagocytic activity of turbot (Scophthalmus maximus) leucocytes: Opsonic effect of antibody and complement - Figueras Huerta, Antonio; Santarém, M. M.; Novoa, Beatriz (Fish & Shellfish Immunology, 1997)
4 páginas, 1 figura, 1 tabla This work was supported by Grant AGF94-1360-CO3-O3 of the Comisión Interministerial de Ciencia y Tecnologıa (CICYT). Maria Santarem thanks the Junta Nacional de Investigaçao Cientıfica e Tecnológica (Portugal) for a research fellowship. Peer reviewed